The impact of coronavirus disease 2019 (COVID-19) on provider use of electronic hand hygiene monitoring technology. (20th August 2021) - Hess, Olivia C. R.; Armstrong-Novak, Jo Dee; Doll, Michelle; Cooper, Kaila; Bailey, Pamela; Godbout, Emily; Stevens, Michael P.; Bearman, Gonzalo
Abstract: The use of an electronic hand hygiene monitoring system (EHHMS) decreased due to the coronavirus disease 2019 (COVID-19) pandemic. We analyzed dispenser use, hand hygiene (HH) badge use, and HH compliance to determine the effect of COVID-19 on EHHMS use and HH compliance. HH product shortages and other pandemic-induced challenges influenced EHHMS use.